Continuous dependence and fixed points for some multivalued operators - Eduard Kirr; Adrian Petrușel (Journal of Numerical Analysis and Approximation Theory, 1997)
In this paper we extend the notion of \(I^0\)-continuity and uniform \(I^0\)-continuity from [2] to set-valued operators. For families of such operators we prove (semi)continuity of the fixed point sets.